Distinguishing Weber from Pseudo Weber Syndrome: A Diagnostic Dilemma- A Case Report - Rashid, Ahmad Akhtar; Khan, Hamza; Rashid, Akhtar; Gill, Rehan (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: Weber Syndrome is typically characterized by ipsilateral oculomotor nerve palsy and contralateral hemiparesis, commonly resulting from mesencephalon (midbrain) lesions. However, we present a unique case of a patient exhibiting classic Weber Syndrome symptoms that were ultimately attributed to distinct underlying causes, leading to a diagnosis of Pseudo-Weber Syndrome. Case Presentation: The patient presented with left-sided hemiparesis and upper motor neuron facial paralysis, initially suggesting a clinical diagnosis of Weber Syndrome. Further radiological investigation revealed a left middle cerebral artery (MCA) infarct with internal capsule involvement as the primary cause of the hemiparesis and facial paralysis involving the contralateral lower half of the face. Additionally, the oculomotor nerve symptoms were traced to uncal herniation, rather than a mesencephalon(midbrain) lesion. Discussion: This case underscores the importance of thorough radiological assessment in patients with Weber Syndrome-like presentations, highlighting the diagnostic challenge in distinguishing Weber from Pseudo-Weber Syndrome. Understanding the varied aetiologies behind similar clinical presentations is crucial for accurate diagnosis and appropriate management.